NEGERI UTAMA DAN PERANNYA DALAM MERAIH KEBAHAGIAAN PERSPEKTIF AL-FARABI - Alamsyah Kaharuddin Manu; Zainab Soraya (Sekolah Tinggi Agama Islam Sadra, 2021)
Happiness is an eternal theme that humans always talk about. Many philosophers talk about happiness, from the ancient Greeks to the times of Islamic philosophers. Al-Farābi, an early Muslim philosopher, offers an interesting view of happiness: Medina al-Fāḍilah as the basis for achieving happiness. Happiness is defined as the highest good that makes man detached from material nature and coexist with immaterial beings forever. The Main State which is likened to a body, has a leader who has achieved human perfection. It is through this leader that the people of Negeri Utama try to build their country together to achieve true happiness. By using the literature study method and researching the existing literature, it is concluded that al-Farabi's main state concept has an important role in the study of political philosophy. A country must have a goal of happiness and talking about the parent country will certainly discuss the concept of leadership, leadership patterns, and forms of the state.